Nilai-Nilai Tauhid dalam Syair Lagu Bimbo dan Implementasinya dalam Kegiatan Kemanusiaan (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2021)
Music is a medium that can be used as a means of conveying monotheistic values, so that it is easily accepted by the community. Its entertaining nature can be used by singers or artists to incorporate the values ​​of tauhid, so that society has indirectly accepted it. The purpose of this study is to analyze the values ​​of tauhid in the Bimbo song lyrics and their implementation. This research uses a qualitative approach. The primary source in this study is the lyrics of the Bimbo song entitled God, Long Prayers, Remembering You, and Do not be Delayed. To analyze the song lyrics, the researcher used content analysis method. The results of this study indicate that: 1). The value of monotheism in the lyrics of the Bimbo song, namely Bimbo through its songs invites and educates people to monotheise Allah in terms of: believing that Allah Swt is God, the Creator of all creatures and maintains all of His creations; believe in and monotheize Allah Swt by concentrating all worship to Him; monotheize Allah by knowing the name and nature of Allah SWT, so that humans can get closer to and know Allah and only hope in Allah SWT, 2). Meanwhile, the form of implementation of tauhid, namely Bimbo, is not only limited to singing and playing music, but also lecturing. And from the results of the author's interview with Sam Bimbo, it turns out that Bimbo's songs also have an impact on other people who listen to them, then make the person feel moved to get closer to Allah SWT. Keywords: Tauhid, Implementation, Bimbo